(3GdgeRI aj HGH GdMeRIs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , (B833 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI ; bGd GdabjQ CMeO Hf GdLRQj GdMeO hGdTcQ dHGQj GdHTQ (B- (3Ke GdUdGI hGdSdGe SQeOG Ydi GdfHj GdYQHj CMeOGs
(3BNQgG (B:s
(3hcdeG JWQaJ geRI cGf gTGe hGbaG cMeRIs
(3BNQg fbhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 227s
(3eYLe GdeDdajf (B1 / 291s
(3GdVhA GddGeY (B2 / 193s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs